Osteoblasts growth behaviour on bio-based calcium carbonate aragonite nanocrystal - Kamba, Abdullahi Shafiu; Abu Bakar @ Zakaria, Md Zuki (Hindawi Publishing Corporation, 2014)
Calcium carbonate (CaCO3) nanocrystals derived from cockle shells emerge to present a good concert in bone tissue engineering because of their potential to mimic the composition, structure, and properties of native bone. The aim of this study was to evaluate the biological response of CaCO3 nanocrystals on hFOB 1.19 and MC3T3 E-1 osteoblast cells in vitro. Cell viability and proliferation were assessed by MTT and BrdU assays, and LDH was measured to determine the effect of CaCO3 nanocrystals on cell membrane integrity. Cellular morphology was examined by SEM and fluorescence microscopy. The results showed that CaCO3 nanocrystals had no toxic effects to some extent. Cell proliferation, alkaline phosphatase activity, and protein synthesis were enhanced by the nanocrystals when compared to the control. Cellular interactions were improved, as indicated by SEM and fluorescent microscopy. The production of VEGF and TGF-1 was also affected by the CaCO3 nanocrystals. Therefore, bio-based CaCO3 nanocrystals were shown to stimulate osteoblast differentiation and improve the osteointegration process.